OPEN ASSESSMENT FOR OPEN SCHOOLING IN THE (POST) PANDEMIC WORLD. A THEORETICAL APPROACH (Proceedings of the International Conference on Education, 2023)
Due to globalization and the unexpected pandemic outburst, the need for educational change and shift to openness came to the fore. Openness confirms the quality of education as a fundamental human right, providing educational opportunities to everyone and under any circumstances. Nonetheless, open educational practices are rarely applied and adopted by schools, and as a result, traditional school education remains outdated, maintaining its narrow and closed character. Student assessment, as an integral part of the educational process, can enhance either school’s openness or closedness. Therefore, the purpose of this paper is to examine – through a literature review of peer-reviewed, topic-related articles – how the implementation of open assessment can contribute to forming an open school, which aims at students’ amelioration and not categorization, according to their scores. The major findings of our study show that open forms of assessment lead to promoting openness within schools, by developing 21st century learner skills in meaningful and authentic ways, as well as values related to democracy, human rights and equity. This paper adds up to the existing literature as it offers an alternative perspective regarding school assessment, which is in alignment with the needs of today’s learners and can function as an assistive tool for opening up school education in the long term.
Keywords: traditional student assessment; open assessment; open schooling; equity; democracy; covid-19 pandemic